2013
DOI: 10.1111/ene.12296
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in thalamic microstructure of migraine without aura patients: a diffusion tensor magnetic resonance imaging study

Abstract: These higher thalamic FA values noted during the interictal period which normalized during an attack are probably related to plastic peri-ictal modifications in regional branching and crossing of fibres. Whether these changes could be considered as the anatomical counterpart of the cyclical functional fluctuations previously observed in the neurophysiology of migraine remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 58 publications
10
103
0
Order By: Relevance
“…Volume changes as evidenced by MRI may be influenced by many different pathophysiological processes, including change of synaptic and neuronal density, abnormal dendritic arborization, abnormalities of white matter within the thalamus, abnormal water content, and many other processes (Vercellino et al, 2009;Sinjab et al, 2013). In the future, it may be useful to combine neuroimaging with electrophysiological recordings to better understand how structural and functional abnormalities are related in migraine (de Tommaso et al, 2014). Electrophysiological methods may also be better suited to determine alterations in the sensory trigeminal-thalamic system at present (de Tommaso et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Volume changes as evidenced by MRI may be influenced by many different pathophysiological processes, including change of synaptic and neuronal density, abnormal dendritic arborization, abnormalities of white matter within the thalamus, abnormal water content, and many other processes (Vercellino et al, 2009;Sinjab et al, 2013). In the future, it may be useful to combine neuroimaging with electrophysiological recordings to better understand how structural and functional abnormalities are related in migraine (de Tommaso et al, 2014). Electrophysiological methods may also be better suited to determine alterations in the sensory trigeminal-thalamic system at present (de Tommaso et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the intralaminar nuclei, including the CM/Pf complex, are relevant for synchronizing/desynchronizing the activity between different brain networks according to behavioral demands (Saalmann, 2014). Interestingly, previous studies have indicated abnormal cortical synchronization patterns in patients with migraine compared with healthy subjects (de Tommaso et al, 2007). Moreover, the CM/Pf nuclear complex projects densely to the striatum and cortex (Goadsby et al, 1993;Benarroch, 2008).…”
Section: Specific Role and Neuroanatomical Connections Of Affected Thmentioning
confidence: 97%
See 2 more Smart Citations
“…148 Moreover, in a diffusion tensor MRI study, our research group found dynamic ictal and inter ictal microstructural variations in the thalamus that were related to the time since the last migraine attack, and seemed to mimic the cyclic neurophysiological changes described above. 149 Collectively, these observations suggest that a search for optimal methods of influencing the cortical tem poral processing of exogenous stimuli that can trigger a migraine attack, or methods for modulating endo genous trigeminal noxious inputs that lead to central sensitization and eventually chronic headache, could result in novel interventions for migraine prevention. The modes of action of anticonvulsants or antidepressants, as well as of other pharmacological or nonpharmacologi cal interventions, such as neuromodula tion methods, should be reconsidered in terms of their ability to nor malize the complex abnormalities of brain connectivity and hyperresponsivity found in patients with migraine.…”
Section: Prospects For Clinical Researchmentioning
confidence: 99%